IMPROVING THE RELIABILITY OF TRANSFORMERS IN DISTRIBUTION NETWORKS (Web of Teachers: Inderscience Research, 2024)
Various methods for improving the reliability of transformers in distribution networks are considered, and the reasons for their reduced service life are analyzed.